Information literacy skills development for teachers (2009)
Acquisition of information literacy skills by teachers and students in this 21st Century Information Age is paramount for their all-round success in life. This paper has X-rayed how different authors conceptualised information literacy skills and the role they can play in the academic, Professional and personal life of individuals. The process of developing the skills by the teachers and the students through Integration of information literacy skills instruction in the school curriculum is well discussed in the paper. The article recommends ways of achieving the goal of developing information literacy skills by teachers and students in Nigerian schools.